Flexural behavior of HDPE tubular beams filled with self-compacting geopolymer concrete. (October 2021) - Kurtoğlu, Ahmet Emin; Hussein, Ali Khalid; Gülşan, Mehmet Eren; Çevik, Abdulkadir
Abstract: This paper proposes a new hybrid composite tubular beam system that consists of an exterior high-density polyethylene (HDPE) tube with interior steel tube and self-compacting geopolymer concrete (SCGC). The flexural behavior of composite tubular beams with SCGC encased in HDPE tubes was investigated experimentally and theoretically. A total of twenty-two specimens was tested, including twelve confined and ten unconfined specimens. The test variables include the presence of confinement (confined or unconfined), HDPE tube thickness and interior diameter, presence of inner steel tube, cross section of inner layer (circular or square), and presence of SCGC filling in inner layer. The failure mode, flexural strength and fracture energy are examined based on measured load–deflection data by four point bending test. Results indicated that the HDPE confinement provided significant enhancement in flexural response and especially the ductility of specimens, demonstrating considerably large plastic deformations before failure. A theoretical methodology was developed to predict the ultimate flexural load capacity. The analysis was conducted based on the combination of classical beam theory and the modification of a previously proposed methodology. Results of the analysis confirmed the high accuracy of proposed methodology in predicting ultimate flexural capacity of HDPE tube-confined beams. Highlights: New type of composite tubular beam system with geopolymer concrete is proposed. Effects of confinement, tube thickness, inner steel tube and concrete filling. Confined specimens show large elastic deformations with high load bearing capacity. Tube thickness has the largest effect on load bearing capacity and fracture energy. Cross section of inner tube and filling with concrete have smaller effects.